Chirping compact stars: gravitational radiation and detection degeneracy with binaries (2023)
ABSTRACT:Abstract. Compressible, Riemann S-type ellipsoids can emit gravitational waves (GWs) with a chirp-like behavior (hereafter chirping ellipsoids, CELs). We show that the GW frequency amplitude evolution of CELs (mass ∼ 1 M⊙, radius ∼ 103 km, polytropic equation of state with index n ≈ 3) is indistinguishable from that emitted by double white dwarfs and by extreme mass-ratio inspirals (EMRIs) composed of an intermediate-mass (e.g. 103 M⊙) black hole and a planet-like (e.g. 10−4 M⊙) companion, in the frequency interval within the detector sensitivity band in which the GW emission of these systems is quasi-monochromatic. For reasonable astrophysical assumptions, the local universe density rate of CELs, double white dwarfs, and EMRIs in the mass range here considered are very similar, posing a detection degeneracy challenge for space-based GW detectors. We outline the astrophysical implications of this CEL-binary detection degeneracy by space-based GW-detection facilities.